Implementation Of Family Hope Program (PKH) in Kerinci Regency during 2015 - 2016 - Lestari, Riski Puspita; Aji, Juhari Sasmito (Sustainability (STPP) Theory, Practice and Policy, 2021)
Poverty is the goal of national development and also have been mandated in the Constitution of Indonesia Namely the Constitution of 1945 of the opening is to prosper throughout Indonesia. In facing the problem of poverty in Indonesia the Government had made policies with the programmes to reduce the problem of poverty. One of them, namely the family Hope programme (PKH) that had been launched by the Government in 2007, where it was judged capable of PKH to address existing problems and in 2014 the Regency of Kerinci is a Regency of jamba who carry out the programmes of family expectations (PKH), in implementation of the Kerinci Regency in the PKH are a variety of problems, such as the escort have difficulty in socialization, the misappropriation of funds, and more. This research uses qualitative, descriptive methods through data collection techniques interviews, observation and documentation. As for the results of the research that has been done by researchers can be concluded that the implementation of the policy of Family Expectations Program (PKH) in Kerinci Regency in 2015-2016 have been conducted properly, the goals, socializing, and channeling the implementation was done according to the provisions and procedures that exist. But in the socialization there is a lack of coordination between the Department of education, the health service, BPS, Bappeda and facilities in its execution also still less. From the research that has been done, the writter recommend in the selection of participants is expected to involve the Government's Martes PKH so right on target in the selection of participants and PKH doing koordinas between related parties implementation of the PKH.